A case study on organization of roof-tile production during the Tang Dynasty: Focusing on tile ends with Lotus patterns unearthed from Ximing Temple. (March 2021) - Lyu, Meng; Gong, Guoqiang; Li, Chunlin
Abstract: Roof tiles are the most frequently unearthed remains from the sites of imperial-period cities in China. These include tile ends, decorated roof tiles designed to attach to the first row of imbrices laid along the eaves. This study investigated a large number of tile ends containing lotus patterns excavated from Ximing Temple in Chang'an, present-day Xi'an, which was once the capital of the Tang Dynasty. In addition to an examination of aspects of tile ends that were controlled consciously by artisans, such as front surfaces, patterns, and sizes, this study also focused on gathering information through an analysis of aspects resulting from the mechanical process such as minor variations in size, pattern, tool marks, and the proportion of the edge to the diameter. We measured the intentional standardization and mechanical standardization of tile ends using the aspects mentioned above, and the degree of standardization in an assemblage can be used to infer the organization of production. This study thus expands on artifact typology to analyze the organization of and changes in tile-end production at the Ximing Temple workshop. With reference to other samples and historical records of the Tang Dynasty, it also provides evidence that can shed light on general cultural variations and socio-economic changes in this period.